Synthesis, structural, spectroscopic and docking studies on (E)-1-Ferrocenyl-3-phenylpropen-1-one by the density functional theory. Issue 5 (24th March 2022) - Amalanathan, M.; Michael Mary, M. Sony; Beatrice, M. Latha; Delphine, S. Mary; Robert, H. Marshan; Twinkle, A. R.; Ratkovic, Zoran; Samson, Y.
ABSTRACT: The complete geometrical parameters of the synthesised compound (E)-1-Ferrocenyl-3-phenylpropen-1-one were calculated by the Density Functional Theory method. The Fourier-transform infrared spectra and Fourier-transform -Raman spectra of (E)-1-Ferrocenyl-3-phenylpropen-1-one molecule were analysed by comparing the experimental results with the theoretical calculations. Natural bond orbital analysis analyses the intramolecular contacts of (E)-1-Ferrocenyl-3-phenylpropen-1-one molecule. Ultraviolet–visible spectra of the (E)-1-Ferrocenyl-3-phenylpropen-1-one molecule have been recorded, and the electronic properties have been computed with the time-dependent density functional theory method. The chemical reactive sites have been revealed by the Fukui function and molecular electrostatic potential analysis. Docking studies were performed for (E)-1-Ferrocenyl-3-phenylpropen-1-one molecule using the molecular docking software with four topoisomerasesfrom Protein Data Bank. In vitro antibacterial assay showed inhibitive growth of (E)-1-Ferrocenyl-3-phenylpropen-1-one molecule against bacterial pathogens staphylococcus aureus and pseudomonas aeruginosa .